Functional performance among active female soccer players after unilateral primary anterior cruciate ligament reconstruction compared with knee-healthy controls - Fältström, A.; Hägglund, M.; Kvist, J. (The American Journal of Sports Medicine, 2017)
Background: Good functional performance with limb symmetry is believed to be important to minimize the risk of injury after a return to pivoting and contact sports after anterior cruciate ligament reconstruction (ACLR). Purpose: This study aimed to investigate any side-to-side limb differences in functional performance and movement asymmetries in female soccer players with a primary unilateral anterior cruciate ligament (ACL)-reconstructed knee and to compare these players with knee-healthy controls from the same soccer teams. Study Design: Cross-sectional study; Level of evidence, 3. Methods: This study included 77 active female soccer players at a median of 18 months after ACLR (interquartile range [IQR], 14.5 months; range, 7-39 months) and 77 knee-healthy female soccer players. The mean age was 20.1 ± 2.3 years for players with an ACL-reconstructed knee and 19.5 ± 2.2 years for controls. We used a battery of tests to assess postural control (Star Excursion Balance Test) and hop performance (1-legged hop for distance, 5-jump test, and side hop). Movement asymmetries in the lower limbs and trunk were assessed with the drop vertical jump and the tuck jump using 2-dimensional analyses. Results: The reconstructed and uninvolved limbs did not differ in any of the tests. In the 5-jump test, players with an ACL-reconstructed knee performed worse than controls (mean 8.75 ± 1.05 m vs 9.09 ± 0.89 m; P = .034). On the drop vertical jump test, the ACL-reconstructed limb had significantly less knee valgus motion in the frontal plane (median 0.028 m [IQR, 0.049 m] vs 0.045 m [IQR, 0.043 m]; P = .004) and a lower probability of a high knee abduction moment (pKAM) (median 69.2% [IQR, 44.4%] vs 79.8% [IQR, 44.8%]; P = .043) compared with the control players` matched limb (for leg dominance). Results showed that 9% to 49% of players in both groups performed outside recommended guidelines on the different tests. Only 14 players with an ACL-reconstructed knee (18%) and 15 controls (19%) had results that met the recommended guidelines for all 5 tests (P = .837). Conclusion: The reconstructed and uninvolved limbs did not differ, and players with an ACL-reconstructed knee and controls differed only minimally on the functional performance tests, indicating similar function. It is worth noting that many players with an ACL-reconstructed knee and controls had movement asymmetries and a high pKAM pattern, which have previously been associated with an increased risk for both primary and secondary ACL injury in female athletes.